Phyllactinia chubutiana: A new species of Erysiphales from Patagonia (Argentina) - Havrylenko M. (2014)
Phyllactinia chubutiana, a parasite on leaves of Lycium chilense (Solanaceae) collected in the arid Patagonian steppe, is proposed as a new species. The new combination Ovulariopsis insolita is introduced for its anamorph previously described as Oidium insolitum. © 2006 The Mycological Society of Japan and Springer-Verlag.